Implementation of peer-assessment system in speaking courses - Rochma, Anis Firdatul; Suharso, Suharso; Sudiyono, Sudiyono; Fitriana, Rahma (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
The ability to speak effectively refers to an individual's capacity to convey thoughts and ideas orally. Various teaching strategies are employed to enhance speaking skills, with traditional methods primarily relying on teacher-driven assessments. However, incorporating peer assessment has emerged as a valuable approach that enables students to identify their strengths and areas for improvement, promoting the development of language proficiency, metacognitive awareness, and related skills. This study aims to implement peer assessment as an alternative evaluative method in the Speaking in Academic Contexts course, which includes both informative and persuasive speech tasks. Quantitative data were analyzed descriptively, with mean and standard deviation calculations comparing peer assessment scores to those assigned by the instructor. The Wilcoxon Signed Ranks Test was applied to determine statistically significant differences between the two sets of scores. Qualitative data, derived from students' reflections, were analyzed using thematic analysis. Overall, students in the Speaking in Academic Contexts course reported positive perceptions of peer assessment, recognizing its potential to enhance their language skills and foster learner autonomy.